Research on the reconstruction of global high-tech mineral industry chain and supply chain - LI Huajiao, LI Zheng, ZHENG Xinxin, CHEN Congxi, ZHANG Yuqi, LIU Meng, MENG Ziyu, HAN Shitong (Ziyuan Kexue)
The underlying resource logic of the current great power competition is gradually shifting from oil competition to competition for high-tech mineral resources. The layout of the high-tech mineral industry chain and supply chain is transitioning from a focus on cost, efficiency, and technology to an emphasis on security, stability, and politics, showing evolutionary characteristics such as diversification and regionalization. Since June 2019, Western countries, including the United States, have gradually established a localized and exclusive resource governance system focused on high-tech minerals. This governance system has undergone a rapid transformation from a loose network of raw material supplying countries (seller’s markets), to a closely linked network among developed countries (buyer’s markets), and then to a supply chain “long-arm jurisdiction” network governed by ESG. Based on a comprehensive review and analysis of the connotations of terms such as high-tech minerals, critical minerals, and strategic minerals, this study provides a systematic definition of the high-tech mineral industry and supply chains. It then focuses on analyzing the competition for high-tech mineral resources among great powers, the trends in the reconstruction of industry chains and supply chains, and the potential risks that the entire industry chain and supply chain may face. Furthermore, from the perspectives of research and management, this study presents relevant frontier issues: (1) The dynamic definition of high-tech mineral resources and the theoretical framework of its industry and supply chains; (2) Scientific interpretation of the competition for high-tech mineral resources and the process of industry and supply chain reconstruction among great powers; (3) Risk assessment, monitoring, and early warning of multiple reconstruction of the primary and recycled resource industry chain and supply chain; (4) Coordinated management and security measures for the primary and recycled resource industry chain and supply chain.